(untitled) (Third Sector Social Economic Review, 2023)
While parties are the most important tools of democracies, far-right parties prevent the deepening of democracies with the hate speech they use. In the transition from the legitimate political arena to the illegal sphere, far-right parties have an important place in the transition from hate speech to hate crimes. The rising vote rates of far-right parties in Europe are seen as one of the most important indicators of increasing support for the far-right. The role of far-right parties is not limited to themselves. Prejudices, discrimination and racism prevalent in society contribute to the increase in hate crimes. Economic and social problems are also among the main reasons for the increase in such crimes. By using these factors in their rhetoric, far-right parties increase their supporters and pave the way for an increase in hate crime rates in the society. After 9/11, Islamophobia entered the agenda of far-right parties seeking new enemies. The reduction of emerging problems to cultural and religious reasons, independent of their structural causes, led to the expansion of political, social and economic conflicts. Modern racism, which emerges as cultural exclusion, manifests itself in the form of restrictive policies against immigrants. The national security agendas of the states overlap with the immigration control programs of xenophobic movements, and the integration measures imposed by the governments also strengthen the Islamophobia of the far right. Better regulation is needed in this area to combat the spread of Islamophobic content through social media.